1987
DOI: 10.1128/jb.169.2.830-838.1987
|View full text |Cite
|
Sign up to set email alerts
|

Lipid acyl chain-dependent effects of sterols in Acholeplasma laidlawii membranes

Abstract: Acholeplasma laidlawii was grown with different fatty acids for membrane lipid synthesis (saturated straightand branched-chain acids and mono-and di-unsaturated acids). The ability of 12 different sterols to affect (i) cell growth, (ii) lipid head group composition, (iii) the order parameter of the acyl chains, and (iv) the phase equilibria of in vivo lipid mixtures was studied. The following two effects were observed with respect to cell growth: (i) with a given acyl chain composition of the membrane lipids, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…This conclusion is strengthened by the metabolic responses to the cholestene by the MGlcDAG and DGlcDAG synthases that were reconstituted together (Figure 7). Here the MGlcDAG and DGlcDAG outputs closely mimicked observations from in vivo experiments, with strong metabolic compensation in packing properties (8,30). The increase in the MGlcDAG synthesis rate brought about by the presence of the (second) DGlcDAG synthase (Figure 7) may be caused by a chan-5518 Biochemistry, Vol.…”
Section: Discussionsupporting
confidence: 72%
“…This conclusion is strengthened by the metabolic responses to the cholestene by the MGlcDAG and DGlcDAG synthases that were reconstituted together (Figure 7). Here the MGlcDAG and DGlcDAG outputs closely mimicked observations from in vivo experiments, with strong metabolic compensation in packing properties (8,30). The increase in the MGlcDAG synthesis rate brought about by the presence of the (second) DGlcDAG synthase (Figure 7) may be caused by a chan-5518 Biochemistry, Vol.…”
Section: Discussionsupporting
confidence: 72%
“…To prepare for the simulation of Txb–lipid II complex formation at the membrane–water interface, a lipid II molecule was partially inserted into a 1-palmitoyl-2-oleoyl-phosphatidyl-ethanolamine (POPE) bilayer, chosen to represent bacterial membranes such as the inner membrane of Escherichia coli ,34 or the plasma membrane of certain Bacillus species 35,36. The inserted lipid II molecule was simulated for 1 μs to capture its membrane-bound configuration.…”
Section: Resultsmentioning
confidence: 99%
“…However, in two studies (Davis et al, 1980; Koblin & Wang, 1981), much higher levels of cholesterol incorporation were reported, 39 and 40 mol %, respectively. These values seem high for A. laidlawii B, particularly since in both of these studies the membrane lipids were enriched in saturated fatty acids, which usually results in lower levels of cholesterol incorporation (typically 12-15 mol %) than with lipids enriched in primarily unsaturated fatty acids (deKruijff et al., 1972Wieslander & Selstram, 1987;Bhakoo & McElhaney, 1988;Rilfors et al, 1987). Using 2H NMR dePakeing methods previously developed (Sternin et al, 1988;Lafleur et al, 1989), we have recently found that membrane hydrocarbon order falls within a defined range if good rates and extents of A. laidlawii growth are to be observed.…”
mentioning
confidence: 92%